EFEITOS DE MODOS DE APLICAÇÃO, DOSES E FONTES DE POTÃSSIO NA PRODUÇÃO DA SOJA - Rosolem, Ciro A.; Nakagawa, João; Machado, José Ricardo; Yamada, T. (REVISTA DE AGRICULTURA, 2020)
EFEITOS DE MODOS DE APLICAÇÃO, DOSES E FONTES DE POTÃSSIO NA PRODUÇÃO DA SOJA